KEMELIMPAHAN DAN KERAGAMAN JENIS PARASITOID HAMA PENGGULUNG DAUN PISANG ERIONOTA THRAX L. DI KABUPATEN LAMPUNG SELATAN - Lestari Wibowo; Indriyati .; Purnomo . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
The abundance and diversity of the parasitoid of banana leaf skipper pest (Erionota thrax L.) in South Lampung Regency. This research was conducted to determine the abundance, diversity, and parasitation ability of several parasitoids of the banana skipper or banana leafroller (Erionota thrax) in South Lampung Regency. This research was carried out with a survey method by taking out samples of larvae and pupae of E. thrax in the District of Natar, Jati Agung, and Tanjung Bintang, South Lampung. Results of the survey showed that there were 8 types of parasitoids recovered from larvae or pupae of E. thrax, i.e. Brachymeria lasus (Chalcididae: Hymenoptera), B. thracis (Chalcididae: Hymenoptera), Charops sp. (Ichneumonidae: Hymenoptera), Casinaria sp. (Ichneumonidae: Hymenoptera), Xanthopimpla sp. (Ichneumonidae: Hymenoptera), Cotesia erionotae (Braconidae: Hymenoptera), and two parasitoids Diptera (Tachinidae and Sarcophagidae). The highest abundance of parasitoid was found in Tanjung Bintang with 171 parasitoids (index of diversity (H’) = 1.0256 and index of evenness (E) = 0.5724). In Natar District, the abundance of parasitoid was 63 parasitoids, but it had a greater H’ value (1.4396) and E-value (0.7398). Meanwhile, in Jati Agung District, the abundance of parasitoid was 56 individuals but the value of H’ was also high, which was 1.012 with the value of E of 0.6064. The percentages of parasitation to the larvae and pupae E. thrax were 55.01% (Tanjung Bintang District), 31.68% (Natar District) and 33.34% (Jati Agung District).